Illocutionary Speech Acts in Indonesian Language Learning at High School - Widiasri, Dewa Ayu (e-Journal of Linguistics; Vol 14 No 2 (2020): e-jl July, 2020)
The purpose of this study is to describe the types of illocution in the form of verbal speech acts between teachers and students in learning Indonesian language at Senior High School 1- Tampaksiring, Gianyar, Bali. This study applied descriptive qualitative analysis with the support of audio-visual recordings technique, observation methods, documentation methods that combined with pragmatics and classification techniques. The results of the study have shown that the types of illocution, with the order of use, are directive function (40%), expressive (25%), assertive (20%), commissive (10%), and declarative (5%) in teacher and student speech acts.